FINANCIAL PERFORMANCE OF INDIAN NSE-LISTED COMPANIES ASSOCIATED WITH MANUFACTURING ACTIVITIES - Das, Priya; Debbarma, Sumanta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study evaluated the financial performance of Indian manufacturing companies using an entropy-based COPRAS approach for 2022. A sample of 18 companies was selected from Nifty 50 firms and assessed based on five key financial ratios. The weights for each financial indicator were measured using the entropy method, and the rankings were performed using the COPRAS approach. It was observed that the debt-equity ratio is the most important performance indicator in the analysis, while the Current Ratio obtained the lowest weightage of 0.061. The ranking results indicate that Coal India Ltd. is the best performer during the period, followed by Bajaj Auto Ltd. and Eicher Motors Ltd. On the other hand, Bharat Petroleum Corpn. Ltd. received the lowest ranking based on the alternatives’ performance score and degree of utility value. The study provides significant insights into the Indian manufacturing industry, efficiency, and areas for improvement for the companies in the sector. The application of MCDM in this context was limited, which encouraged this study.